Unraveling Fossilization Among Moroccan EFL Learners: The Impact of Achievement Motivation, Multilingualism, and Cultural Exposure - EL Yazid Iraqi; Chaimae Fertat; Hind Brigui (Journal of English Language Teaching and Linguistics, 2025)
This study investigates interlanguage fossilization among Moroccan EFL learners, with focus on how achievement motivation, multilingualism, and cultural exposure effect the endurance of language errors. Using a mixed-methods approach, data were collected from 100 students across different Moroccan universities. The study used quantitative findings from questionnaires and fossilization detection tasks with qualitative data gathered through semi-structured interviews. Results show a clear inverted relationship between achievement motivation and fossilized errors, learners with higher motivation lean to make fewer grammatical mistakes. The data also show that multilingual learners who consistently immerse with English through cultural activities like watching films, joining language exchanges, or consuming online content demonstrate fewer persistent errors. Semi-structured interviews shed further light on how students’ linguistic backgrounds and cultural experiences form the way they discern their own language development. Although the findings highlight the complex relationship of psychological, linguistic, and socio-cultural factors in second language learning, they are limited by the study’s cross-sectional design, reliance on self-reported data, and a sample restricted to university students, which may affect generalizability. The study calls for practitioners to build motivation, embrace multilingual strengths, and reinforce active cultural engagement.